Required dose of sugammadex or neostigmine for reversal of vecuronium‐induced shallow residual neuromuscular block at a train‐of‐four ratio of 0.3 - Jing He; Huan He; Xing Li; Mei Sun; Zhihao Lai; Bo Xu (Wiley, 2022)
Abstract Residual shallow neuromuscular block (NMB) is potentially harmful and contributes to critical respiratory events. Evidence for the optimal dose of sugammadex required to reverse vecuronium‐induced shallow NMB is scarce. The aims of the present study were to find suitable doses of sugammadex and neostigmine to reverse a residual vecuronium‐induced NMB from a time of flight (TOF) ratio of 0.3-0.9 and evaluate their safety and efficacy. In total, 121 patients aged 18-65 years were randomly assigned to 11 groups to receive placebo, sugammadex (doses of 0.125, 0.25, 0.5, 1.0, or 2.0 mg/kg), or neostigmine (doses of 10, 25, 40, 55, or 70 μg/kg). The reversal time of sugammadex and neostigmine to antagonize a vecuronium‐induced shallow residual NMB (i.e., TOF ratio of 0.3) and related adverse reactions were recorded. Several statistical models were tested to find an appropriate statistical model to explore the suitable doses of sugammadex and neostigmine required to reverse a residual vecuronium‐induced NMB. Based on a monoexponential model with the response variable on a logarithmic scale, sugammadex 0.56 mg/kg may be sufficient to reverse vecuronium‐induced shallow residual NMB at a TOF ratio of 0.3 under anesthesia maintained with propofol. Neostigmine may not provide prompt and satisfactory antagonism as sugammadex, even in shallow NMB.